Biodigestão Anaeróbia dos Resíduos da Agroindústria de Citrus em consórcio com dejetos de Suínos - Santos, Ícaro Victor Valério de Souza (2016)
Today, the scenario of the world and brazilian energy matrix is of great difficulty, due to increased demand for fossil fuels causing instabilities in prices and in the fuel sector, as well as serious environmental risks to the whole population. The difficult time comes driving the search for new sources of renewable and clean energy such as biogas. In this way, this work aimed to evaluate the anaerobic biodigestion from the residue of agro-industry of citrus using inoculum from swine waste water. We used 12 anaerobic batch type reactors, fed with different concentrations of residues of citrus being inoculated with the swine waste. Were testadas4 citrus residue concentrations (25%, 50%, 75% and 100%) during 60 days. It was observed that the increase in the concentration of residues of citrus caused a decrease in pH and metanogênica activity specifies fact that can be assigned inhibiting substance (D-Limonene) present in citrus peel, which when not undergo a pre-treatment can negatively affect the work of metanogênicas microorganisms. However, the proportion of 25% of citrus residue with 10% p.10536–10540 of swine waste for better production of methane when no pre-treatment of the citrus.